Choosing a meal to increase your appeal: How relationship status, sexual orientation, dining partner sex, and attractiveness impact nutritional choices in social dining scenarios. (1st February 2019) - Baker, Michael; Strickland, Andie; Fox, Nicole D.
Abstract: The impact of social context on dining choices was investigated via an online experiment. Participants were assigned to different hypothetical dining partners of the same or opposite sex and varying levels of attractiveness (or no partner in a control condition) and were then asked to indicate what foods they would order if they were dining with this individual. Following a food selection task, the attractiveness of the hypothetical partner was rated, followed by the measurement of personal characteristics such as current relationship status, participant sex, and sexual orientation. Results revealed that among heterosexual participants, relationship status, partner sex, and partner attractiveness interacted to influence the total number of calories ordered. Heterosexual male and female participants who were not currently in a relationship and had been assigned to an opposite-sex dining partner tended to order fewer calories the more attractive that they perceived their partner to be. The findings of this study build upon previous research on social influences on dining behavior by examining the roles of relationship status and dining partner attractiveness on nutritional decision-making.